STUDY OF THE IMPACT OF FORCED MIGRATION ON DEMOGRAPHICS, ECONOMIC DEVELOPMENT AND SOCIAL SITUATION IN UKRAINE - NAPORCHUK, Denys (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the problem of enforced population relocation, a process of obtaining different answers to the issues of forced migrants, refugees, and persons with temporary protection. It examines the features and trends of voluntary and forced population migration, especially the case of Ukrainians who emigrated because of war and its effect on the demographic situation in Ukraine and the countries accepting refugees, especially in the European Union. The European Union, on the other hand, has become one of the main migration destinations for Ukraine’s citizens, including those who are seeking refugee status or temporary protection. There are many difficulties for the EU and Ukraine in the future because of this. For the EU this implies the need to create a good migration policy that would guarantee the inclusion of migrants into the society and the economy and at the same time would make sure the security and would avoid the conflicts. For Ukraine, it is essential to have a plan for the return of its citizens who had to leave the country due to the war, so that they can take part in the process of rebuilding the country and help in its development. The prime factor that needs to be looked at is the economic influence of migration. It can be good and bad for the economy of the sending and the receiving countries to be together. On the other hand, migrants can fill the labor gap in areas where there are not enough locals to work and they can also bring new concepts, skills and technologies. At the same time, massive numbers of migrants can cause a fierce competition in the labor market and consequently lead to the decrease of wages and the worsening of the work conditions of the locals. Hence, the policies that will be created should be able to have the best for the economy and at the same time the economy will be stable. The other aspect to take into account is the designing of the ways for the migrants to return to their country of origin. This is a crucial matter for the country from which expulsion takes place, which may lose its skilled workforce and its considerable economic contribution, and for the migrant, who may find it hard to adjust to a new country. The return policies should accommodate the reversion of migrants to their homeland and the rehabilitation of them.